(untitled) (Journal of Pakistan Orthopaedic Association, 2026)
Objective: To assess the functional outcome of pediatric femoral shaft fracture treated with Elastic nail using flynn’s criteria. Methods: This descriptive study was conducted on twenty children with femoral shaft fractures treated with Titanium elastic nail from January 2013 to December 2014. The mean age was 10.25 years and the mean follow up period was 12 months. Results: In a mean time of 7.5 weeks, all patients get united. There were 17 (85%) Excellent, 2 (10%) satisfactory and 1 (5%) poor result. Conclusion: Titanium elastic nailing is safe and effective method of treating femoral shaft fracture in paediatric age group. It is less invasive with fewer complications.